Конституційно-організаційні засади протидії російській пропаганді в умовах війни - Озель, Віталіна Іванівна; Пашинська, Діана Юріївна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
Abstract. The report is devoted to the study of the constitutional foundations of legal influence in the field of countering Russian propaganda. In the conditions of full-scale Russian armed aggression against Ukraine, propaganda is used by the enemy as a weapon. The basis for counteracting external influence and interference in the internal politics of Ukraine is laid down in the Constitution of Ukraine, in Articles 2, 17, 37. Two laws were adopted defining the principles of banning Russian propaganda and its imperial influence in 2022 and 2023. Ukraine recognizes propaganda as a means of waging hybrid warfare, which is used by Russia on a par with the informational and psychological operations of the enemy.